2018
DOI: 10.1016/j.sdentj.2018.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of clinical efficacy of locally delivered 0.2% Thymoquinone gel in the treatment of periodontitis

Abstract: Significant changes in clinical and biochemical parameters were achieved in the current study. Hence, it is concluded that intracrevicular application of 0.2% Thymoquinone gel could be a beneficial adjunct to SRP in treating chronic periodontitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 28 publications
(33 reference statements)
1
20
0
Order By: Relevance
“…Administration of TQ can occur through several routes, including systemic intraperitoneal, intravenous, oral subacute and sub-chronic administration, besides the localized drug delivery of TQ [ 6 , 60 , 61 ]. In the current investigation the reviewed in vivo studies reported the local periodontal application of 0.1–0.2% TQ gel [ 62 , 63 , 64 ] and similarly in the form of fabricated periodontal chips containing 2.5 mg of TQ [ 65 ]. One animal investigation reported systemic TQ administration by gastric feeding, at a rate of 10 mg/kg/d [ 66 ].…”
Section: Nigella Sativa and Thymoquinone As Thementioning
confidence: 99%
See 2 more Smart Citations
“…Administration of TQ can occur through several routes, including systemic intraperitoneal, intravenous, oral subacute and sub-chronic administration, besides the localized drug delivery of TQ [ 6 , 60 , 61 ]. In the current investigation the reviewed in vivo studies reported the local periodontal application of 0.1–0.2% TQ gel [ 62 , 63 , 64 ] and similarly in the form of fabricated periodontal chips containing 2.5 mg of TQ [ 65 ]. One animal investigation reported systemic TQ administration by gastric feeding, at a rate of 10 mg/kg/d [ 66 ].…”
Section: Nigella Sativa and Thymoquinone As Thementioning
confidence: 99%
“…In vitro studies on TQ or NS extract effects on periodontal diseases and bacteria administered solutions of 2% NS extract [ 63 ] and 0.01–10% concentrations of TQ [ 67 , 68 ]. All tested concentrations and routes of drug delivery showed significant periodontal health-favoring outcomes in terms of clinical periodontal parameters as plaque index (PI), gingival index (GI), probing pocket depth (PPD), bleeding on probing (BOP), clinical attachment levels (CAL) [ 62 , 65 , 66 ], as well as molecular parameters as gingival crevicular fluid alkaline phosphatase levels (GCF-ALP) [ 66 ] and cytokine/chemokine levels [ 63 ]. Microbiological and histological parameters similarly showed significant improvements as observed in biofilm formation and inflammatory cell infiltration (ICI) [ 66 , 67 , 68 , 69 ].…”
Section: Nigella Sativa and Thymoquinone As Thementioning
confidence: 99%
See 1 more Smart Citation
“…Dental plaque is more complex and diverse among individuals and under in vivo conditions. Although a suppressive effect of TQ on alveolar bone loss and dental plaque accumulation has been demonstrated in a rat periodontitis model (22) and clinical study (38), respectively, these studies did not monitor microbiome alterations in saliva or dental plaque. Animal and clinical studies that focus on FN, a keystone periodontal pathogen, will provide new insights into the mechanisms for prophylactic and therapeutic effects of TQ on periodontal disease.…”
Section: Discussionmentioning
confidence: 99%
“…7 In previous clinical studies, TQ showed antiepileptic action in children and its intracrevicular application has been found to be beneficial in treating chronic periodontitis. 8,9 The reduced form of TQ, thymohydroquinone (THQ), is also considered as perspective biological active compound with antibacterial, antifungal, anti-inflammatory, antioxidative, and antitumor effects. 10,11 The inhibitory activity for acetylcholinesterase was also observed in this substance.…”
Section: Introductionmentioning
confidence: 99%